Dorsal Lunate Facet Fracture Reduction Using a Bone Reduction Forceps - Lans, Jonathan; Alvarez, Josefina; Kachooei, Amir R.; Ozkan, Sezai; Jupiter, Jesse B. (Journal of Wrist Surgery, 2019)
Background The dorsal lunate facet fragment represents part of a complex articular injury of the distal radius and is challenging to reduce through a standard volar approach. We propose reduction through a standard volar approach and intraoperative dorsal lunate facet reduction using a bone forceps. To evaluate the postoperative reduction, we used computed tomography (CT) scan.Methods We retrospectively included 60 patients with a median follow-up of 44 weeks. Fracture reduction was evaluated using pre- and direct postoperative CT scans of the wrist, measuring the articular gap and step of the sigmoid notch. The range of motion was evaluated clinically by the treating physician. Bivariate analysis was performed to compare pre- and postoperative radiographic measurements and to compare wrist range of motion.Results When comparing the injured with the uninjured wrist, there was a significant difference in flexion, extension, pronation, and supination. In 87% of the patients, there was complete radiographic reduction of the fracture.Conclusion This study shows that dorsal ulnar lunate facet fracture fragments in distal radius fractures can be reduced through a standard volar approach with the help of an intraoperative bone reduction forceps. Using wrist CT, we showed that 87% of the patients with a dorsal ulnar lunate facet fragment had a postoperative articular step or gap of <1 mm.Level of Evidence: This is a level IV, therapeutic study.
Keywords: radiographic evaluation; radius fracture; volar plate fixation